From purchase to consumption of bivalve molluscs: A qualitative study on consumers' practices and risk perceptions. (February 2019) - Crovato, Stefania; Mascarello, Giulia; Marcolin, Silvia; Pinto, Anna; Ravarotto, Licia
Abstract: Worldwide bivalve production has increased significantly in recent years. Bivalve meat is recommended in dietary regimens due to the benefits associated with their consumption but, at the same time, is internationally recognized as a potential vehicle for outbreaks of foodborne disease. To reduce food risk exposure, consumers must pay close attention when purchasing, handling and consuming bivalves. This study aimed to collect information on consumers' perceptions and practices related to bivalve purchasing, managing and consumption at home. A focus group methodology was adopted to better understand consumers' food practices and risk perceptions regarding molluscs. Four focus groups involving 42 consumers were conducted in Veneto and Marche region. The core analysis was then applied to each focus group discussion in order to identify, categorize and rank the information collected. The most important factors that came to light during the focus groups concerned the personal reasons for preparing bivalves at home; the place of purchase; the elements guiding consumers when purchasing bivalves; the bivalve preparation, cooking and storage conditions at home; the consumption of raw molluscs and the health risks; the consumers' categories most at risk; and the production chain control by the authorities. The data reported in the article can provide useful information to public authorities working on food safety for developing effective risk communication strategies. Highlights: Consumers play a crucial role in food risk reduction. The focus group methodology collected information from Italian consumers. The study analysed consumers' purchasing, handling and consumption of bivalves. The data provide useful information for implementing risk communication activities.